Nonconventional and vernacular construction materials : characterisation, properties and applications - Harries, Kent A. 1967-; Sharma, Bhavna (Woodhead Publishing, 2016)
Nonconventional and Vernacular Construction Materials: Characterisation, Properties and Applications provides a comprehensive repository of information on materials science and the modern structural engineering application of ancient, vernacular, and nonconventional building materials, with leading experts contributing chapters that focus on current applications and the engineering of these construction materials. Opening with a historic retrospective of nonconventional materials, Part One includes a review of vernacular construction and a discussion of the future directions for nonconventional and vernacular materials research and applications. Chapters in Part Two focus on natural fibers, including their application in cementitious composites, non-cementitious composites, and strawbale construction. In Part Three, chapters cover the use of industrial by-products and natural ashes in cement mortar and concrete, and construction using soil-cement blocks, clay-based materials, adobe and earthen materials, and ancient stone masonry. Timber, bamboo, and paper construction materials are investigated in the final section of the book.
Keywords: Building materials.; elektronické knihy; electronic books